The Mountain Region during the Period of Rule of Pahalawani Mamāleek 1199-1218 - Hassan, Darwesh Yousef; Saleh, Hadar Saleem (Journal of Duhok University, 2019)
This research deals with an analytical historical study of the most difficult periods of in the history of the Mountain Region, which was the period of rule of Pahalawani Mamluks of this region, where was ruled by four of the Atabek Mamluk tycoons Jihan Pahalwan Al- Ildkizi  and they were Kokgih , Etigimish, Menkily and Aglamish during the period between (495-614 AH/ 1199-1218 AD).The research also seeks to determine the goals of the Abbasid Caliphate through its continuous intervention in this region and its attempts to bring stability for this region. It also tried to create a loyal entity for their Caliphate by establishing diplomatic relations with the leaders of two of these Mamluks or by using military force as well as making use of its allies in the region, such as the Ildkizian and Ismailian or the owner of Arbailo and Mosul in order to eliminate the rebels as they did before with Minkily and Aglamish.